Protocol for a multicentre, prospective, observational cohort study of variation in practice in perioperative analgesic strategies in elective laparoscopic colorectal surgery: the LapCoGesic Study. Issue 9 (6th September 2016) - ,; Burnell, Phillippa; Coates, Rachael; Dixon, Steven; Grant, Lucy; Grey, Matthew; Griffiths, Ben; Jones, Mike; Madhavan, Anantha; McCallum, Iain; McClean, Ross; Naru, Karen; et al.
Abstract : Introduction: Laparoscopic surgery combined with enhanced recovery programmes has become the gold standard in the elective management of colorectal disease. However, there is no consensus with regard to the optimal perioperative analgesic regime in this cohort of patients, with a number of options available, including thoracic epidural spinal analgesia, patient-controlled analgesia, subcutaneous and/or intraperitoneal local anaesthetics, local anaesthetic wound infiltration catheters and transversus abdominis plane blocks. This study aims to explore any differences in analgesic strategies employed across the North East of England and to assess whether any variation in practice has an impact on clinical outcomes. Methods and analysis: All North East Colorectal units will be recruited for participation by the Northern Surgical Trainees Research Association (NoSTRA). Data will be collected over a consecutive 2-month period. Outcome measures will include postoperative pain score, postoperative opioid analgesic use and side effects, length of stay, 30-day complication rates, 30-day reoperative rates and 30-day readmission rates. Ethics and dissemination: Ethical approval for this study has been granted by the National Research Ethics Service. The protocol will be disseminated through NoSTRA. Individual unit data will be presented at local meetings. Overall collective data will be published in peer-reviewed journals and presented at relevant surgical meetings.